2008
DOI: 10.1093/jjco/hyn100
|View full text |Cite
|
Sign up to set email alerts
|

A Questionnaire Survey of Physicians' Perspectives Regarding the Assessment of Chemotherapy-induced Peripheral Neuropathy in Patients with Breast Cancer

Abstract: The PNQ appears to be a useful instrument for the diagnosis and grading of CIPN, as well as for clinical decision-making regarding treatment modifications secondary to CIPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…Moreover, the pnq is designed to clearly delineate between no interference and interference with defined activities of daily living. Hence, it is a useful instrument, with high acceptance by physicians 37 . Several researchers have reported that pnq sensory and motor scores are correlated with the fact and the fact-Gynecologic Oncology Group-Neurotoxicity questionnaires (r = 0.66 and 0.51 respectively) 38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the pnq is designed to clearly delineate between no interference and interference with defined activities of daily living. Hence, it is a useful instrument, with high acceptance by physicians 37 . Several researchers have reported that pnq sensory and motor scores are correlated with the fact and the fact-Gynecologic Oncology Group-Neurotoxicity questionnaires (r = 0.66 and 0.51 respectively) 38 .…”
Section: Discussionmentioning
confidence: 99%
“…First, it relied on self-reported data and did not include objective measures of nerve function such as neurologic exams or nerve conduction studies. However, numerous studies have demonstrated the reliability and validity of self-reporting tools for evaluating the severity of neuropathic symptoms in patients receiving chemotherapy 37,38,55,56 , and selfreported neuropathy has been included as an outcome measure in numerous studies 3,37,38 . A second limitation of the study is the cross-sectional nature of the data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The compliance in reporting by patients and physicians in the study was exceptional, exceeding 90% throughout the study. Additionally, when asked about the diagnostic and clinical utility of the PNQ, 84% of the physicians reported that the PNQ was helpful in the diagnosis and assessment of patients at risk for CIPN [18].…”
Section: Assessment Of Chemotherapy-induced Neuropathymentioning
confidence: 99%
“…O questionário apresentou uma boa aceitação e benefícios para extrair informações sobre NPIQ de acordo com a visão médica. O PNQ destaca a importância em avaliar a presença e efeito da NPIQ nas AVDs pelos pacientes e profissionais de saúde, e as percepções dos profissionais de saúde pelo questionário ressaltaram a utilidade para coletar informações, diagnosticar e graduar a NPIQ, além de auxiliar na tomada de decisões em relação a modificações no tratamento (KUROI et al, 2008). Outros estudos divergem sobre o questionário, uma vez que, os participantes relataram dificuldades na compreensão do questionário PNQ, ao confundirem os itens referentes aos sintomas relacionados à quimioterapia com os relacionados aos procedimentos cirúrgicos (SIMÃO et al, 2012).…”
Section:  Peripheral Neuropathy Scale (Pns) -Almadrones Et Al (2004)unclassified